The impact of advanced practitioners on patients in acute care—A mini review - Bauernfeind, Lydia; Fels, Milena; Dahlmann, Philipp; Rester, Christian; Sterr, Fritz (Frontiers in Disaster and Emergency Medicine, 2024)
Background: Acute patient care is becoming increasingly complex due to various factors (e.g. demographic changes, multimorbidity, organizational changes). Educating healthcare professionals as advanced practitioners at Master's level is one response to these challenges. Meanwhile, there are several empirical insights into advanced roles. Aim: To provide an overview onthe impact of advanced practitioners on acute care patients’ outcomes and safety. Methods: We conducted a mini-review. Therefore, a systematic literature search was carried out in the four databases Medline, CINAHL, Cochrane Library, and PEDro. After four researchers screened the results and extracted the data independently, the included studies were analyzed thematically and clustered along patients’ outcomes. The results are presented narratively. Results: 4,332 records were identified in the systematic search, and 67 articles were included in our review. Of these, the majority (n = 57) addressed the nursing profession. Advanced practitioners demonstrated an overall positive impact on acute care patients. They improved patients’ vital signs, and reduced their mortality and adverse events (e.g. thrombosis, pneumonia, pressure injury). In addition, they shortened patients’ length of stay and waiting times, and reduced admission rates. Patient satisfaction also increased after their implementation. When being compared to physicians, advanced practitioners in acute care demonstrated similar to equal patient outcomes and safety. Conclusion: The identified studies highlight the benefits of advanced practitioners for acute care patients. While most studies were conducted in emergency departments or intensive care units, further research concerning other acute settings (e.g. psychiatry) or clinical conditions (e.g. cognitive impairment) is recommended.